Our racist heart? : an exploration of unconscious prejudice in everyday life - Beattie, Geoffrey (New York : Routledge, 2013)
Few people today would admit to being a racist, or to making assumptions about individuals based on their skin colour, or on their gender or social class. In this book, the author, a psychologist, asks if prejudice, more subtle than before, is still a major part of our everyday lives. He suggests that implicit biases based around race are not just found in small sections of our society, but that they also exist in the psyches of even the most liberal, educated and fair minded of us. More importantly, the book outlines how these 'hidden' attitudes and prejudices can be revealed and measured, and how they in turn predict behaviours in a number of important social situations. This book takes a fresh look at our racial attitudes, using new technology and experimental approaches to show how unconscious biases influence our everyday actions and thinking. These results are brought to life using the author's own experiences of class and religious prejudice in Northern Ireland, and are also discussed in relation to the history of race, racism and social psychological theory.
Challenged by History. Approaches and avoidances ; A room steeped in the past ; Early lessons in prejudice: spoken and unspoken ; Who needs the Negro? ; The nature of prejudice. -- A Pipeline to the Soul? The times they are a-changin' (or not, as the case may be) ; The inner conflict ; How much of our attitude is unconscious? ; Measuring the unconscious ; A new way into our unconscious attitude ; By-passing the conscious mind. -- The Project Itself: Are We Implicitly Racist? A new test of implicit ethnic bias ; New data on possible implicit ethnic bias ; Am I a racist? ; Why aren't we saving the planet? Another example of unconscious bias in action ; How ethnicity and implicit attitudes may affect shortlisting for university posts ; So what can we do about any of this? -- Implicit biases operating in the academy: the detailed results.
Includes bibliographical references and index.
Keywords: Prejudices; Racism -- Psychological aspects; Prejudices; Racism -- Psychological aspects